Pengenalan Bentuk Geometri Melalui Media Puzzel pada Anak di TK Al Mursalat 2 Padang - Rahma Calista; Dadan Suryana; Nenny Mahyudin (Journal on Education, 2023)
Educational media is everything that can be used to deliver educational materials so that they stimulate the mind, interest, thoughts and feelings of students (students) in the educational program to achieve educational goals. Educational media is a tool or other material that provides a comprehensive type of information and can support the teaching and learning process. Learning to introduce geometric shapes at an early age certainly requires proper educational planning and support. Therefore, to increase the child's ability to introduce geometric shapes, you can use complex support. Assembling geometric shape puzzles can improve children's cognitive abilities. Philosophy (skills) is associated with the ability to learn and solve children's problems. In addition, it can improve children's social skills. Using content analysis methods and textbooks, this research attempts to explain the complex support for introducing geometric shapes in early childhood.